2021
DOI: 10.1021/acs.energyfuels.1c00785
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of CeO2 in Stabilization of Multivalent Mn Species on α-MnO2/Mn3O4/CeO2/C Surface for Enhanced Electrocatalysis

Abstract: A hybrid heteronanostructure of α-MnO 2 /Mn 3 O 4 /CeO 2 with the atomic-level coupled nanointerface entrenched in Vulcan carbon is reported and explored for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). CeO 2 plays an essential role in increasing the surface Mn 2+/3+/4+ in α-MnO 2 /Mn 3 O 4 /CeO 2 /C for ORR/OER processes. It shows enhanced bifunctional activity, superior to that of the benchmark 20 wt % Pt/C and Pd/C catalysts. It displays an ORR onset potential of −0.13 V (vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…17 CeO 2 is a potential additive for improving the activity of a transition MO owing to its unique oxygen storage capacity, oxygen transfer ability, and highly active Ce 3+ /Ce 4+ redox couple. 18,19 Equation 1 shows the ability of CeO 2 to reversibly switch between the +3 and the +4 oxidation states: 18,20 The properties of CeO 2 defined it as an "oxygen buffer" that regulates the surface oxygen density by capturing or eliminating oxygen in O 2 -rich or O 2 -lean conditions, respectively, thereby generate oxygen vacancies and promotes rapid electron transfer across the oxide−oxide/carbon interface. 20−22 For instance, Liu et al 20 synthesized Co 3 O 4 −CeO 2 / KB, which was found to be very efficient as compared to that of single MO counterparts due to the strong synergistic interaction between Co 3 O 4 and CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 CeO 2 is a potential additive for improving the activity of a transition MO owing to its unique oxygen storage capacity, oxygen transfer ability, and highly active Ce 3+ /Ce 4+ redox couple. 18,19 Equation 1 shows the ability of CeO 2 to reversibly switch between the +3 and the +4 oxidation states: 18,20 The properties of CeO 2 defined it as an "oxygen buffer" that regulates the surface oxygen density by capturing or eliminating oxygen in O 2 -rich or O 2 -lean conditions, respectively, thereby generate oxygen vacancies and promotes rapid electron transfer across the oxide−oxide/carbon interface. 20−22 For instance, Liu et al 20 synthesized Co 3 O 4 −CeO 2 / KB, which was found to be very efficient as compared to that of single MO counterparts due to the strong synergistic interaction between Co 3 O 4 and CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the formation of robust heterogeneous interfaces between different phases of MOs and their synergetic effects which promotes easy electron transfer . CeO 2 is a potential additive for improving the activity of a transition MO owing to its unique oxygen storage capacity, oxygen transfer ability, and highly active Ce 3+ /Ce 4+ redox couple. , Equation shows the ability of CeO 2 to reversibly switch between the +3 and the +4 oxidation states: , …”
Section: Introductionmentioning
confidence: 99%
“…The influence of multivalent states of Ni (+2, +3), Ce (+3, +4), and W (0, +4, +5, +6, +x) on electrocatalysis activity is mainly based on the following aspects. (1) The internal conversion between multivalent states in Ni (+2, +3), Ce (+3, +4), and W (0, +4, +5, +6, +x) leads to rapid charge transfer for carriers, which enhances the conversion of H‐H 2 and the dissociation of chemical bonds between O−H to improve the catalytic activity [54–58] . (2) The synergistic effect and alloying between the multivalent states of transition metals Ni, Ce, and W enhance the catalytic activity [57–59] .…”
Section: Resultsmentioning
confidence: 99%
“…[54][55][56][57][58] (2) The synergistic effect and alloying between the multivalent states of transition metals Ni, Ce, and W enhance the catalytic activity. [57][58][59] (3) The existence of oxygen vacancies will expose more active sites, which will promote the interaction between activated electrons and protons to improve the catalytic activity. [60,61] The X-band paramagnetic resonance (EPR) in Figure S4 also displays a significantly stronger EPR signal with g factor close to 2 in NiCeWO x -1 compared to that of NiCeWO x -2.…”
Section: Chemelectrochemmentioning
confidence: 99%
“…Precious metals like Pt and Pd supported on CeO 2 exhibit good catalytic activity toward the ORR [21][22][23][24], but precious metals are quite challenging for commercialization [25,26]. Although there is much research dealing with CeO 2 -supported catalysts for the ORR, there are very few studies focusing on the importance of oxygen vacancy in doped CeO 2 [27][28][29]. Furthermore, the abundance of oxygen vacancies in CeO 2 favors O 2 adsorption and oxygen conductivity due to the coexistence of Ce 4+ and Ce 3+ , which contribute to the CeO 2 -supported electrocatalyst in the ORR [30,31].…”
Section: Introductionmentioning
confidence: 99%